Vectorial reconstruction of NIR-VIS optical field by XUV interferometry - Carpeggiani, P. A.; Reduzzi, M.; Comby, A.; Ahmadi, H.; Kühn, S.; Calegari, F.; Nisoli; Frassetto, F.; Poletto, L.; Hoff, D.; Ullrich, J.; Schröter, C. D.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
Field and polarization sensitive optical processes require precise knowledge of the electric field vector E(t) of the interacting pulse at every time instant. A novel measurement technique with attosecond resolution is described and demonstrated experimentally.
CRIS-Team Scopus Importer:2023-04-20